Prevalence of specific anti-skin autoantibodies in a cohort of patients with inherited epidermolysis bullosa - Tampoia, Marilina; Bonamonte, Domenico; Filoni, Angela; Garofalo, Lucrezia; Morgese, Maria Grazia; Brunetti, Luigia; Di Giorgio, Chiara; Annicchiarico, Giuseppina (Orphanet journal of rare diseases, 2013)
Background Inherited epidermolysis bullosa (EB) is a group of skin diseases characterized by blistering of the skin and mucous membranes. There are four major types of EB (EB simplex, junctional EB, dystrophic EB and Kindler syndrome) caused by different gene mutations. Dystrophic EB is derived from mutations in the type VII collagen gene (COL7A1), encoding a protein which is the predominant component of the anchoring fibrils at the dermal-epidermal junction. For the first time in literature, we have evaluated the presence of anti-skin autoantibodies in a wider cohort of patients suffering from inherited EB and ascertained whether they may be a marker of disease activity. Methods Sera from patients with inherited EB, 17 with recessive dystrophic EB (RDEB), 10 with EB simplex (EBS) were analysed. As much as 20 patients with pemphigus vulgaris, 21 patients with bullous pemphigoid and 20 healthy subjects were used as controls. Anti-skin autoantibodies were tested in all samples with the Indirect Immunofluorescence (IIF) method and the currently available ELISA method in order to detect anti-type VII collagen, anti-BP180 and anti-BP230 autoantibodies. Results The mean concentrations of anti-type VII collagen autoantibodies titres, anti-BP180 and anti-BP230 autoantibodies were statistically higher in RDEB patients than in EBS patients. The sensitivity and specificity of the anti-type VII collagen ELISA test were 88.2% and 96.7%. The Birmingham Epidermolysis Bullosa Severity score, which is used to evaluate the severity of the disease, correlated with anti-skin autoantibodies titres. Conclusions The precise pathogenic role of circulating anti-skin autoantibodies in RDEB is unclear. There is a higher prevalence of both anti-type VII collagen and other autoantibodies in patients with RDEB, but their presence can be interpreted as an epiphenomenon.